2019
DOI: 10.1088/1361-6404/aafe94
|View full text |Cite
|
Sign up to set email alerts
|

An improved parallel-plate capacitor apparatus for the estimation of dielectric constants of solid materials

Abstract: In this paper, we present the design and implementation of a modified parallel-plate capacitor (PPC) and its mathematical derivation, which may well be incorporated as a challenging problem in physics textbooks covering topics on capacitance and dielectrics. The dielectric material under test (MUT) fills the empty space between the plates of the PPC, and a very thin layer of air is trapped between the uneven surfaces of the metallic capacitor plates and the MUT. It has been reported in the literature (Grove T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Table 3 shows the excellent contribution of the new approach when Equation ( 36) is used. However, errors can be numerous when utilizing Equation (7). We finally note that the error levels in both techniques (use of the eigenvalue and the new approach) are identical.…”
Section: 0mentioning
confidence: 84%
See 2 more Smart Citations
“…Table 3 shows the excellent contribution of the new approach when Equation ( 36) is used. However, errors can be numerous when utilizing Equation (7). We finally note that the error levels in both techniques (use of the eigenvalue and the new approach) are identical.…”
Section: 0mentioning
confidence: 84%
“…This is because the correction causes the gap observed in the final results in the propagation constant, but not in the characteristic impedance. For instance, taking off Z v in Equation (7), and according to the Brews equation for Q-TEM mode, as mentioned in [47]:…”
Section: 0mentioning
confidence: 99%
See 1 more Smart Citation
“…The arrangement of dielectric constant and impedance analyzer measurements can be performed at low frequencies when the wavelength is much larger than the sample dimensions. Recently, Riaz et al [12] reported an idea about a modified capacitor structure that offers a remedy to determine the dielectric constant of a dielectric MUT, placed in between its metal plates, in an elegant way to bypass the effect of a very delicate trapped thin air layer. The general shape of the arrangement that is used in this paper (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The general shape of the arrangement that is used in this paper (i.e. parallel plate capacitor with circular electrodes, four screws, and plastic spacers) is similar to the apparatus described by Riaz et al [12]. However, this method does not take the effect of fringing fields into consideration and needs to accurately consider the impact of screws in the calculations.…”
Section: Introductionmentioning
confidence: 99%